1999
DOI: 10.7589/0090-3558-35.4.741
|View full text |Cite
|
Sign up to set email alerts
|

Organochlorine Contaminant Levels in Eskimo Harvested Bowhead Whales of Arctic Alaska

Abstract: Organochlorine (OC) levels in liver and blubber of 20 bowhead whales (Balaena mysticetus) collected during the Eskimo subsistence harvest at Barrow (Alaska, USA) in 1992 and 1993 are presented. Liver sum DDT (lipid weight) was significantly greater in male whales than in females. Most of the organochlorines measured were at higher levels in longer (older) than in shorter (younger) males. For female bowhead whales, hexachlorobenzene and lipid levels decreased and other OC levels did not change significantly wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 25 publications
2
21
0
Order By: Relevance
“…Significant positive correlations between age and SPCBs, SDDTs, and Schlordanes have also been found in male bowhead whales (Balaena mysticetus) [58,59] and male North Atlantic right whales (Eubalaena glacialis) [46]. In northeast Atlantic minke whales (Balaenoptera acutorostrata), significantly higher concentrations of the same three contaminant classes were found in mature males compared with juvenile males [60].…”
Section: Ecological and Biological Factors Affecting Contaminant Loadsmentioning
confidence: 79%
“…Significant positive correlations between age and SPCBs, SDDTs, and Schlordanes have also been found in male bowhead whales (Balaena mysticetus) [58,59] and male North Atlantic right whales (Eubalaena glacialis) [46]. In northeast Atlantic minke whales (Balaenoptera acutorostrata), significantly higher concentrations of the same three contaminant classes were found in mature males compared with juvenile males [60].…”
Section: Ecological and Biological Factors Affecting Contaminant Loadsmentioning
confidence: 79%
“…The traditional diet of the indigenous inhabitants of Arctic and subarctic regions of North America includes large quantities of fish, birds, and marine mammals whose tissues may contain a variety of industrial environmental contaminants and toxins, including mercury and chemical pollutants such as PCBs, dioxin, and other persistent organic pollutants (POPs) (O'Hara et al 1999;Kuhnlein and Chan 2000;Mallory et al 2004;Muir et al 2006;Reist et al 2006;Kelly et al 2007;Krey et al 2015). Studies have found high levels of mercury and POPs in indigenous peoples of the North American Arctic, where subsistence food chains are the primary source of exposure to environmental contaminants.…”
Section: Environmental Toxins and Contaminantsmentioning
confidence: 97%
“…Research has demonstrated high concentrations of potentially toxic substances (e.g., organochlorines used as pesticides, perfluorinated chemicals and polychlorinated biphenyls, mercury, and others) have been found in a many marine mammal species from a diversity of locations (Fossi, et al, 2004;Hall, et al, 2006;Hart, et al, 2008;Sascha K. Hooker, et al, 2008;O'Hara, Krahn, Boyd, Becker, & Philo, 1999;Wintle, Duffield, Barros, Jones, & Rice, 2011). Research has indicated an increase in marine mammal disease associated with bioaccumulation of these substances in some species (Hall, et al, 2006;Tabuchi, et al, 2006).…”
Section: Toxic Pollutionmentioning
confidence: 99%